The analysis of Austrian business cycle theory from complexity economics approach - Lanzafame, Alessandra; Bernat, Lukáš; Pavlík, Ján, 1956-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2014)
This thesis analyzes the Austrian business cycle theory (ABCT) from the Complexity Economics approach. Complexity Economics is an approach which comes from the complexity science. It has started to develop since 1980s' in Santa Fe Institute, the leading institution engaging in the research of complexity. In the thesis I mention the terms which are bound to Complexity Economics, for example emergence, the "bottom-up", self-organization, bounded rationality etc. The evolution of the markets, networks and nonlinear dynamics are included in Complexity Economics as well. Complexity Economics views an economy as a dynamical system which never reaches the equilibrium unlike the Traditional Economics approach which main focus is on the general equilibrium of the economy. Another difference would be the way of modelling economies in which Complexity Economics is leaving the unrealistic assumptions because it utilizes the agent-based simulations which enable to do that. In the thesis I also focus on the similarities between Austrian and Complexity Economics, for example the heterogeneity of the agents or the emergence of the price system. These and others similarities are then applied in the analysis of ABCT which serves as an example of demonstration that Austrian Economics could provide the theoretical framework for Complexity Economics which aspires to become a new paradigm in economics.
Vedoucí práce: Lukáš Bernat
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses